2008
DOI: 10.1161/circulationaha.107.739243
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty Strategies in ST-Segment–Elevation Myocardial Infarction

Abstract: A s reviewed in part I of this report, 1 primary PCI without antecedent fibrinolytic therapy has become widely accepted as the preferred reperfusion modality for patients with ST-segment-elevation myocardial infarction (STEMI) presenting at suitably equipped tertiary facilities. However, primary percutaneous coronary intervention (PCI) is not offered at Ն50% of US hospitals, and many of those that do are unable to offer primary PCI as an around-the-clock service. Primary PCI also is less widely available in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 163 publications
(142 reference statements)
0
11
0
1
Order By: Relevance
“…Reperfusion therapy is the cornerstone for treating acute STEMI 2 . Effective reperfusion in STEMI can be achieved by either fibrinolytic therapy or primary Percutaneous coronary intervention (PCI) without antecedent fibrinolysis (also generally known as primary angioplasty) 3 . Fibrinolysis and PCI may also be combined in a variety of ways, depending on the timing of PCI after fibrinolytic administration, the clinical condition of the patient, and whether PCI is applied routinely or selectively after lytic therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reperfusion therapy is the cornerstone for treating acute STEMI 2 . Effective reperfusion in STEMI can be achieved by either fibrinolytic therapy or primary Percutaneous coronary intervention (PCI) without antecedent fibrinolysis (also generally known as primary angioplasty) 3 . Fibrinolysis and PCI may also be combined in a variety of ways, depending on the timing of PCI after fibrinolytic administration, the clinical condition of the patient, and whether PCI is applied routinely or selectively after lytic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrinolysis and PCI may also be combined in a variety of ways, depending on the timing of PCI after fibrinolytic administration, the clinical condition of the patient, and whether PCI is applied routinely or selectively after lytic therapy. Randomized trials have collectively demonstrated enhanced survival and freedom from major adverse cardiovascular events with primary PCI compared with fibrinolysis, and as a result, the expeditious performance of primary PCI has become the preferred reperfusion modality for patients with STEMI presenting at appropriately equipped centers 3 . Primary Percutaneous coronary intervention generally produces better outcomes than fibrinolysis but is not widely available.…”
Section: Introductionmentioning
confidence: 99%
“…The most important factor affecting cardiovascular outcome in the setting of ST-elevation myocardial infarction (STEMI) is rapid restoration of myocardial reperfusion, which is typically achieved by primary percutaneous coronary intervention (pPCI). 1 When pPCI is not readily available, administration of a thrombolytic agent is a reasonable alternative. In both scenarios, there is need for adjunctive therapy to reduce ischemic and reperfusion injury.…”
Section: Résumémentioning
confidence: 99%
“…Contudo, evidências consistentes atuais obtidas a partir de trabalhos bem conduzidos 11,15,16,[18][19][20][21] e com a incorporação do uso de stents demonstram a eficácia e a segurança da ICP eletiva e precoce (preferencialmente inferior a 24 horas, e com possível benefício até 72 horas após a fibrinólise bem--sucedida), com redução significativa das taxas de morte e reinfarto, quando comparadas à estratégia conservadora guiada pela presença de sintomas ou isquemia induzida em testes funcionais. A comparação com atrasos superiores a 72 horas ainda não foi estabelecida.…”
Section: Tabela 4 Preditores Independentes De Insucesso E De Eventos unclassified